Growing community forests : practice, research, and advocacy in Canada - Smith, Peggy; Broad, Gayle; Bullock, Ryan, 1974-; Palmer, Lynn (Catherine Lynn) (University of Manitoba Press, 2017)
"Canada is experiencing an unparalleled crisis involving forests and communities across the country. While municipalities, policy makers, and industry leaders acknowledge common challenges such as an overdependence on U.S. markets, rising energy costs, and lack of diversification, no common set of solutions has been developed and implemented. Ongoing and at times contentious public debate has revealed an appetite and need for a fundamental rethinking of the relationships that link our communities, governments, industrial partners, and forests. The community forest is one path that promises to build social, economic, and ecological resilience. This model provides local control over common forest-lands in order to activate resource development opportunities, benefits, and social responsibilities. Implementing community forestry in practice has proven to be a complex task, however: there are no road maps or well-developed and widely-tested models for community forestry in Canada. But in settings where community forests have taken hold, there is a rich and growing body of experience to draw on. Growing Community Forests brings leading researchers, practitioners, Indigenous representatives, government representatives, local advocates, and students together to share resources, and tools to forest communities, policy makers, and industry."--